ANALYSIS OF MICROSTRUCTURE AND HARDNESS OF WELDED JOINTS OF DISSIMILAR STEEL OF AISI 1018 - AISI 304 - Gilang Gumilar; Imin Abdulah; Rochim Suratman; Asep Ridwan Setiawan (Center for Science & Technology of Advanced Materials - National Nuclear Energy Agency, 2019)
This research studies the microstructure and hardness property of shield metal arc welding (SMAW) from dissimilar metals between austenitic stainless steel (SS) AISI 304 and low carbon steel (LCS) AISI 1018 using E308 filler metal. The procedure used was LCS-to-LCS welding carried out without post weld heat treatment (PWHT) and SS-to-SS welding followed by PWHT at a temperature of 1000ÚC and holding time for 12 minutes. Then, it was followed by shock cooling in aqueous media. The difference in PWHT stages in the two procedures is expected to affect the microstructure and hardness of the welding results. This was conducted to find out more precise procedures in the SMAW technique for welding dissimilar metals like AISI 304 with AISI 1018 so that the risk of chromium carbide precipitate formation and the low hardness of welded joints can be reduced. The results showed there were chromium carbide precipitates in the heat-affected zone (HAZ) of AISI 304, grain enlargement in the HAZ area of both steels, as well as the formation of the ferrite delta phase in the welding area by LCS-to-LCS welding. While the value of hardness in the HAZ area of AISI 304 has decreased, increases occur in the HAZ area of AISI 1018 in all welding conditions. In addition, PWHT treatment can increase the hardness on the AISI 1018 side due to the formation of the martensite phase, decrease in the hardness value on the AISI 304 side, and the reduced ferrite delta phase and the number of chromium carbide precipitates.